(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to identifying the relationship between the use of pricing strategies and enhance of customer satisfaction in Study in the Syrian trading corporation. By identifying the extent of the impact of each dimensions of pricing strategies, by determining the extent to which both the pricing strategies dimensions and the basic requirements of the application of pricing strategies affect customer satisfaction, the researcher relied on the prescriptive approach and the descriptive approach as a general approach to research, the questionnaire was distributed to 384 person from customer in the Syrian trading corporation like Mean, and this study concluded several results, the most important of which was a moral relationship between the use of pricing strategies and the customer satisfaction, and this relationship is acceptable and positive, and is due to the lack of human resource skills and an inappropriate price programme, the researchers have reviewed many important results and made several suggestions and recommendations, the most important of which was the need to develop an appropriate strategy for the use of pricing strategies supporting its operations within the overall strategy of the organization and following up on its implementation and evaluation in order to achieve the basic objectives of the organization.